Determination of phase velocity and attenuation of surface acoustic waves with improved accuracy - Thomann, R.; Johannes, Thomas; Ruile, Werner; Weigel, Robert (Proceedings of IEEE Ultrasonics Symposium, 1998)
The phase velocity and the attenuation of surface acoustic waves (SAW) are determined for Rayleigh waves on free and metallized quartz substrates. The measurement setup and the evaluation procedure based on the direct modeling of the phase for the transmitted signal are discussed. The used method is compared to other evaluation techniques. The results for the phase velocity are given and compared to theoretical values determined with a boundary element method (BEM). Parameter values for an improved model are extracted for the phase velocity as well as for the attenuation. The model is applied to the simulation of TCF-resonators and a comparison between experiment and simulation is performed
elib2cris::1512001600,thomann1998